Understanding morphology - Haspelmath, Martin (Hodder Education, 2010)
This introduction to morphology assumes no prior knowledge of linguistics and presents the field of morphology in an accessible way. Emphasis is put on presenting a range of morphological phenomena from a wide variety of languages.